Soft Soil Improvement by Electroosmotic Consolidation - Kaniraj, Shenbaga R. (International Journal of Integrated Engineering, 2014)
Many laboratory experiments and field trials have shown the potential of electroosmotic consolidation in strengthening of soft clays. However, there are no detailed studies on the effectiveness of electroosmotic consolidation in peat and organic soils. The paper discusses first the electrokinetic reactions that occur during electrokinetic treatment and the material and treatment parameters that affect the effectiveness of the treatment.  A review of the laboratory studies is presented. Salient features of the laboratory experimental studies to investigate the effectiveness of the electroosmosis technique in improving peats and an organic soil from Sarawak are then presented. The influence of selected treatment parameters on the electroosmosis phenomenon is also discussed.